Correlation between 50-gram Glucose Challenge Test and Neonatal Birth Weight - Suntaree Tongchalam; Kamol Pataradool (The Royal Thai College of Obstetricians and Gynaecologists, 2017)
Objectives: To determine the correlation between the 50 gram glucose challenge test (50-g GCT) and neonatal birth weight.Materials and Methods: The study comprised of 1879 women who underwent 50-g GCT at 24-28 weeks of gestation and delivered term infants. We determined the correlation between 50-g GCT by percentile and neonatal birth weight by using Pearson's correlation. ROC analysis was used to determine the threshold of 50-g GCT for predicted low birth weight and macrosomia infants.Results: The correlation coefficient between 50-g GCT by percentile and neonatal birth weight yielded a result of 0.885 (strong positive correlation). Using ROC analysis, 50-g GCT level ≥ 130 mg/dl predicted macrosomia infants with a sensitivity of 41%, specificity 72%, positive predictive value (PPV) 2% and negative predictive value (NPV) 99%. 50-g GCT level ≤ 105 mg/dl predicted low birth weight infants with a sensitivity of 40%, specificity 65%, PPV 6% and NPV 95% respectively. Conclusion: There is a positive correlation between 50-g GCT and neonatal birth weight. 50-g GCT can be used as predictor for macrosomia infants and low birth weight infants.